Tribal Women’s Livelihood In Goa: A Daily Struggle With The Nature And The Nurture - Velip, Priyanka (2016)
Life for tribal women has become a daily struggle due to inflation and the high cost of living in ‘touristic’ Goa as well as government policy regarding their traditional source of livelihood – namely kumeri or shifting cultivation. This has been a common practice among the tribal communities in several parts of India. It has been called by different names, for example jhum cultivation in North India, slash and burn, swidden agriculture etc. In Goa, shifting cultivation is locally known as kumeri cultivation or kaamat in Konkani. This paper is an attempt to document the daily struggles of the women in my own community the Velip community, which is considered as one of the Tribal communities of Goa. Tribal communities seem to be closer to nature because of geographical settlement and therefore they are highly dependent on nature as a means of livelihood. But now days because of government policy, forest laws, etc., the community has been denied access to land and other natural resources making survival by this traditional source of livelihood difficult. The present paper deals with the necessity of the tribal people especially poor Velip women who are more dependent on natural resources as means of livelihood and whose search for alternates is the highlight of this paper. Being from the Velip community, this paper has a personal connection with me as I have lived through the challenges of women from different generations within this tribal community.